Thigh abscess following alternate-site continuous glucose monitoring sensor placement - Kristy M Shaeer; Raechel T White; Benjamin Lord; Tina L Pham; Sarah Kimble; Erin L Reynolds; Jennifer Teeters; Kevin Cowart (American Journal of Health-System Pharmacy, 2026)
Abstract Purpose To describe a methicillin-susceptible Staphylococcus aureus (MSSA) thigh abscess following alternate-site placement of a continuous glucose monitor (CGM) sensor and to highlight safety considerations associated with off-label device use in patients with poorly controlled diabetes. Summary A 49-year-old man with uncontrolled type 2 diabetes (glycated hemoglobin, 11.3%) was referred to an ambulatory care pharmacist for diabetes management. The patient placed the sensor on his upper thigh due to prior dislodgement from the upper arm. Three days later, the patient presented with a painful, erythematous, fluctuant 4.5 x 5 cm abscess at the sensor insertion site. Initial incision and drainage (I&D) was performed and oral sulfamethoxazole/trimethoprim was prescribed. Four days later, he returned with worsening pain and impaired ambulation requiring repeat I&D. Wound cultures grew MSSA. Management additionally included wound packing, topical mupirocin, and continuation of sulfamethoxazole/trimethoprim, with clinical improvement noted after the second I&D procedure. Cutaneous complications with CGM use are typically mild, infrequent, and most often involve contact or irritant dermatitis rather than infection. Reports of CGM-associated skin infections are rare, and none have been reported following sensor placement at unapproved insertion sites. Conclusion This case underscores the potential for a skin and soft tissue infection following off-label CGM placement, especially in patients with uncontrolled hyperglycemia. Pharmacists play a critical role in reinforcing appropriate device use, identifying early signs of infection, and coordinating interdisciplinary care to mitigate device-related complications.